Push and pull factors affecting college students' satisfaction with yoga courses: A case study of colleges and universities in Shenyang - Wei, Yuanyuan; Wan, Xia (Technium Social Sciences Journal, 2023)
In the research process, the methods of literature, interview, Delphi, questionnaire and mathematical statistics were used.From the perspective of push and pull theory, this paper studies the countermeasures to improve students' satisfaction in yoga courses.The satisfaction of yoga courses in Shenyang's colleges and universities is at the middle level, among which the satisfaction of "yoga teaching ability" and "classmate relationship" is relatively high; The satisfaction of "yoga teaching content and teaching method" and "course assessment" is relatively low. On the whole, the satisfaction of yoga teaching has great room for improvement.Through factor analysis and regression analysis, it is concluded that the thrust factor can be expressed by six indicators: improving physical fitness, improving body shape, optimizing interpersonal relationships, hobbies, challenging oneself, and achievements, of which improving physical fitness has the greatest impact; The pull factor can be expressed by six indicators: teacher's own factor, teaching content, teaching method, teaching assessment, teaching effect and teaching environment, of which the teacher's own factor has the greatest impact.Push and pull theory can be used to improve the satisfaction of yoga courses in colleges and universities. In terms of thrust, awaken the thrust factor and improve the satisfaction of yoga courses with the help of internal impetus; In terms of tension, optimize the tension factors and improve the satisfaction of yoga courses with the help of external tension.